LITERATURE REVIEW: PENGARUH KULIT SALAK ( SALACA ZALACCA) TERHADAP GLUKOSA DARAH - Ditte Ayu Suntara (Sekolah Tinggi Pariwisata Mataram, 2023)
Diabetes Mellitus (DM) is a metabolic disorder characterized by stages such as chronic hyperglycemia with disturbances in carbohydrate, fat and protein metabolism caused by defects in insulin secretion, insulin action or both. Along with the development of science, there are many new discoveries that direct the treatment of diabetes by using functional foods and changing lifestyles, one of which is herbs. One of the herbs that can control blood sugar levels is to use zalacca peel herbs (Salacca Zalacca). Purpose, to analyze the bark of the fruit of Salak (Salacca Zalacca) as an anti-diabetic T2. Literature Review Design, Data source: Search using Porquest database, PubMed Central, Google Scholar, articles on topics published in Indonesian and English from 2018-2023. Method Review: Search for articles using PICOS with keywords that match the writing. Articles were selected by journal selection, abstract selection by inclusion criteria, exclusion so that journals were found that could be reviewed. Literature review results of 6 articles that have been selected and then categorized into 2 Characteristics of zalacca peel consisting of 3 articles Compounds in Salak Fruit Peel (Weningtyas et al., 2023), (Ermi Girsang., 2017), (Saleh et al., 2021 ) And 3 articles about zalacca peel as anti-diabetic (Marzuki et al., 2022), (Husnul Khotimah et al., 2021), (Silalahi et al., 2021). Overall conclusion Salak fruit peel is one of the herbal plants that has an antidiabetic effect. This is supported by the many compounds in salak skin that can treat diabetes. Salak bark acts as a lowering of blood sugar levels, an inhibitor of α-glucosidase, regeneration of β-pancreatic cells and an increase in insulin sensitivity